2004
DOI: 10.1145/1015864.1015890
|View full text |Cite
|
Sign up to set email alerts
|

Component-based technologies for end-user development

Abstract: Component-based software development (CBSD) involves multiple roles. Framework builders create the infrastructure for components to interact; developers identify suitable domains and develop new components for them; application assemblers select domain-specific components and assemble them into applications; and end users employ component-based applications to perform daily tasks [7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 8 publications
0
53
0
Order By: Relevance
“…Although the scientists in this study were no longer acting as professional end user developers, we feel that the study has its place in this paper, because the provision of a library of components is often mooted as a means by which software engineers might support professional end user developers, see, for example [8] and [9]. This study made it clear that the provision of such a library is not without problems, as we shall discuss briefly in section 4.…”
Section: The Space Scientistsmentioning
confidence: 94%
“…Although the scientists in this study were no longer acting as professional end user developers, we feel that the study has its place in this paper, because the provision of a library of components is often mooted as a means by which software engineers might support professional end user developers, see, for example [8] and [9]. This study made it clear that the provision of such a library is not without problems, as we shall discuss briefly in section 4.…”
Section: The Space Scientistsmentioning
confidence: 94%
“…Although Mørch's paper did not focus on the web components world, it was the first to deal with building blocks as they are used in the most successful WEUD tools today. Mørch et al [37] later identified the need to create RIAs to support routine work by EUPs, although they included other roles in the development process, such as, for example, advanced programmers to assemble and configure the parts used. This is a job that EUPs could do themselves if they had access to the right mechanisms and simple, general-purpose but at the same time fully functional, component models, as illustrated by the success of some of today's WEUD tools [17,38].…”
Section: Related Work: Existing Solutions For End-user Developmentmentioning
confidence: 99%
“…Our approach follows the lines of end-user software engineering proposed by Mørch et al [6]. Specifically, Pantagruel is based on a compositional approach, where the user connects components (i.e., , sensors, actuators, and controllers) together to form an application.…”
Section: End-user Development For Home Automationmentioning
confidence: 99%
“…Easing the programming of applications for assisting users in their everyday life has been a dominant trend in the home automation research community [1,2,3,4,5,6]. These applications aim to address the user needs by automating their daily tasks in various areas of the home automation domain, such as assisted living, home security, and energy management.…”
Section: Introductionmentioning
confidence: 99%